Coal Waste Powder Amendment and Arbuscular Mycorrhizal Fungi Enhance the Growth of Jabon (Anthocephalus cadamba Miq) Seedling in Ultisol Soil Medium - Sri Wilarso Budi; Fiona Christina (JOURNAL OF TROPICAL SOILS, 2013)
Coal powder waste application on low nutrient media is expected to be able to increase plant growth and to improve Arbuscular mycorrhizal fungi (AMF) development. The objective of this research was to determine the effect of coal waste powder on the growth of Anthocephallus cadamba Jack and AMF development grown on ultisol soil. Two factors in a completely randomised experimental design was conducted under greenhouse conditions and Duncan Multiple Range Test was used to analyse of the effect the treatment. The first factor was ultisol soil ammended with coal waste powder (control, soil amanded with coal waste 5%, soil amanded with coal waste 10% and soil amanded with coal waste 15%) and the second factor was AMF inoculation (uninoculated control, inoculated with Gigaspora margarita). Plant height, diameter, shoot dry weight, percentage of AMF colonization and nutrient uptake were measured in this experiment. Results of this study showed that coal amendment and AMF when applied separately significantly increased height, diameter, shoot dry weight, root dry weight and nutrient uptake of 12 weeks A. cadamba seedling, but when the coal waste powder and AMF were combined the plant growth parameters were lower than those applied separately but significantly higher than control. The application of coal waste powder or AMF in ultisol soil could increase A. cadamba growth and development.[How to Cite : Budi SW and F Christina. 2013. Coal Waste Powder Amendment and Arbuscular Mycorrhizal Fungi Enhance the Growth of Jabon (Anthocephalus cadamba Miq) Seedling in Ultisol Soil Medium. J Trop Soils, 18 (1): 59-66. doi: 10.5400/jts.2013.18.1.59][Permalink/DOI: www.dx.doi.org/10.5400/jts.2013.18.1.59]